CFD analysis of an evacuated solar still - Ismail, Ahmad Faris; Ahmed, Mirghani Ishak; Abakrb, Yousif A. (IIUM Press, 2011)
A mathematical model for an evacuated solar still is presented in this work. Fluent software is used to model and simulate the evaporation and condensation processes inside the solar still. The simulation results showed the transient state of the evaporation and condensation inside the still and the vapour stream lines inside the solar still. Simulation results showed vapour path lines patterns similar to those visualized experimentally in previous literature.